Pengaruh Debt Equity Ratio, Price Earning Ratio, dan Return on Asset Terhadap Harga Saham pada Sektor Tambang Tahun 2020 - Ali, Muhammad Habiburrohman Mukhlish; Mukaram (Applied Business and Administration Journal, 2022)
This study is intended to see the direction, significance and influence of the Debt Equity Ratio (DER), Price Earning Ratio (PER), and Return on Assets (ROA) on stock prices in the mining industry on the IDX in 2020 quarters 1 to 3. The method used namely quantitative descriptive. In this method, the data used is data from a second party, or secondary data, obtained from information on the Indonesia Stock Exchange (IDX) and the company's financial statements. The population in this study are all issuers in the mining industry listed on the BEI in 2020, of which there are 49. The number of samples taken is 46 because there are 3 issuers that have problems in financial statements and some have moved sectors. Multiple linear regression analysis and hypothesis testing were carried out with the f test and t test which resulted in the conclusion that DER had a negative and insignificant effect, ROA and PER had a positive and insignificant effect on stock prices with a significance level above 0.05.